2021
DOI: 10.1186/s12889-021-11312-8
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and associated factors during the COVID-19 epidemic among community non-medical anti-epidemic Workers of Wuhan, China

Abstract: Background Since the outbreak of Coronavirus Disease 2019 (COVID-19) in December 2019, community non-medical anti-epidemic workers have played an important role in the prevention of COVID-19 in China. The present study aimed to assess sleep quality and its associated factors among community non-medical anti-epidemic workers. Method A survey was conducted using anonymous online questionnaire to collect information from 16 March 2020 to 24 March 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Some of these studies delved into the effects on the population of childcare [22], remote working [23], work-family reconciliation [24], food insecurity and dietary quality [25], sleep quality [26], leisure and sport [27]. In turn, these studies have been able to focus on the general population [28], as well as on specific segments, such as the elderly [29,30], chronic patients [31], adolescents [6], women [32], or in directly affected unions, such as health workers [33], teachers [34], etc.…”
Section: Habits Routines and Time Dedication In Times Of Covid-19mentioning
confidence: 99%
“…Some of these studies delved into the effects on the population of childcare [22], remote working [23], work-family reconciliation [24], food insecurity and dietary quality [25], sleep quality [26], leisure and sport [27]. In turn, these studies have been able to focus on the general population [28], as well as on specific segments, such as the elderly [29,30], chronic patients [31], adolescents [6], women [32], or in directly affected unions, such as health workers [33], teachers [34], etc.…”
Section: Habits Routines and Time Dedication In Times Of Covid-19mentioning
confidence: 99%
“…The majority of studies have revealed that health care workers suffered significantly more stress than the general population ( 55 , 56 ). And non-medical anti-epidemic workers in China were also found under huge stress and high exposure risks in the battle against the epidemic ( 57 , 58 ). The inconsistent results can be explained from two aspects: On the one hand, anti-epidemic workers faced challenges such as inadequate virus knowledge, a shortage of personal protective equipment and work-overload at the beginning of the outbreak ( 59 ), which undoubtedly added to their stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the fight against the COVID-19 pandemic, community workers have made a unique contribution to restricting the spread of the pandemic ( Paul et al, 2020 ; Si et al, 2021 ). In mainland China, their significant efforts have included communicating pandemic prevention knowledge, offering psychological counseling, disinfecting public areas and public facilities, providing services for the elderly and the disabled, and investigating potential risks ( Miao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%